Rolling Scheduling Method considering Shiftable Demand Respond Resources. (23rd February 2021) - Lin, Zhengchong; Gao, Feng; Song, Junwen; Lin, Changsheng; Xu, Boyang; Liu, Qiliang; Qiao, Weizhuo; Bao, Yuqing
Abstract : In order to deal with the fluctuation of the renewable energy, this paper proposes rolling scheduling strategy taking into account the capacity of load-side resources. By considering the energy characteristics of shiftable loads, an improved rolling scheduling model is proposed by adopting a full-cycle scheduling and adding periodic power constraints. By this way, the accuracy of the scheduling can be improved. The testing examples verified that the proposed rolling scheduling method can reflect the long-time benefit and therefore result in better performance.